Modelling pulmonary microthrombosis coupled to metastasis: distinct effects of thrombogenesis on tumorigenesis - Colin E. Evans; Asis Palazon; Jingwei Sim; Petros A. Tyrakis; Alice Prodger; Xiao Lu; Saria Chan; Pär-Ola Bendahl; Mattias Belting; Love Von Euler; Helene Rundqvist; Randall S. Johnson; et al. (Biology Open, 2017)
Thrombosis can cause localized ischemia and tissue hypoxia, and both of these are linked to cancer metastasis. Vascular micro-occlusion can occur as a result of arrest of circulating tumour cells in small capillaries, giving rise to microthrombotic events that affect flow, creating localized hypoxic regions. To better understand the association between metastasis and thrombotic events, we generated an experimental strategy whereby we modelled the effect of microvascular occlusion in metastatic efficiency by using inert microbeads to obstruct lung microvasculature before, during and after intravenous tumour cell injection. We found that controlled induction of a specific number of these microthrombotic insults in the lungs caused an increase in expression of the hypoxia-inducible transcription factors (HIFs), a pro-angiogenic and pro-tumorigenic environment, as well as an increase in myeloid cell infiltration. Induction of pulmonary microthrombosis prior to introduction of tumour cells to the lungs had no effect on tumorigenic success, but thrombosis at the time of tumour cell seeding increased number and size of tumours in the lung, and this effect was strikingly more pronounced when the micro-occlusion occurred on the day following introduction of tumour cells. The tumorigenic effect of microbead treatment was seen even when thrombosis was induced five days after tumour cell injection. We also found positive correlations between thrombotic factors and expression of HIF2α in human tumours. The model system described here demonstrates the importance of thrombotic insult in metastatic success and can be used to improve understanding of thrombosis-associated tumorigenesis and its treatment.